Desert locusts threaten again - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
If grasshoppers, and particularly the Senegal locust, caused much less damage this year than was foreseen, the desert locust (see SPORE No. 1) more than made up for it. Originating in Ethiopia, a new invasion of these incredibly destructive insects...